CORRELATION AND PATH ANALYSIS IN GROUNDNUT(Arachis hypogaea L.) UNDER ORGANIC AND CONVENTIONAL FERTILIZER MANAGEMENTS - M. MANJUBHARGAVI; M. SHANTHI PRIYA (The Journal of Research ANGRAU, 2016)
Correlation and path analysis was conducted in 44 genotypes of groundnut with two fertilizer managements viz., organic and conventional. The association analysis in both the managements indicated significant positive association of pod yield plant-1, mature pods plant-1, number of pods plant-1, primary branches plant-1, days to 50% flowering, harvest index, 100 seed weight, shelling percentage and protein content with kernel yield per plant under both the managements, indicating the possibility for simultaneous selection of these characters towards the improvement of kernel yield. Path analysis revealed high positive direct effects of pod yield plant-1 and shelling percentage under both organic and conventional fertilizer managements and significant positive correlation of other traits with kernel yield was due to positive indirect effect via these traits. Hence, selection would be more effective through these traits to improve kernel yield under both the environments